Early Gesture Provides a Helping Hand to Spoken Vocabulary Development for Children with Autism, Down Syndrome, and Typical Development. Issue 3 (27th May 2017) - Özçalışkan, Şeyda; Adamson, Lauren B.; Dimitrova, Nevena; Baumann, Stephanie
ABSTRACT: Typically developing (TD) children refer to objects uniquely in gesture (e.g., point at a cat) before they produce verbal labels for these objects ("cat"). The onset of such gestures predicts the onset of similar spoken words, showing a strong positive relation between early gestures and early words. We asked whether gesture plays the same door-opening role in word learning for children with autism spectrum disorder (ASD) and Down syndrome (DS), who show delayed vocabulary development and who differ in the strength of gesture production. To answer this question, we observed 23 18-month-old TD children, 23 30-month-old children with ASD, and 23 30-month-old children with DS 5 times over a year during parent–child interactions. Children in all 3 groups initially expressed a greater proportion of referents uniquely in gesture than in speech. Many of these unique gestures subsequently entered children's spoken vocabularies within a year—a pattern that was slightly less robust for children with DS, whose word production was the most markedly delayed. These results indicate that gesture is as fundamental to vocabulary development for children with developmental disorders as it is for TD children.